Technical note: Reduction of radiation dose using ultrasound guidance during transjugular intrahepatic portosystemic shunt procedure - Livingstone, Roshan S; Keshava, Shyamkumar N (Indian Journal of Radiology and Imaging, 2011)
The transjugular intrahepatic portosystemic shunt (TIPS) procedure for decompression of the portal venous system generally performed under fluoroscopic guidance has undergone continuous technical modifications recently. Due to the length of the procedure, the fluoroscopy times are reasonably high, thus increasing the risk from ionizing radiation. Radiation doses were measured for 19 patients using dose area product (DAP) meter. The average DAP value for the TIPS procedure was 63.86 Gy cm 2 (21.12-117.07). Radiation doses to patients can be reduced with the use of USG guidance and intermittent fluoroscopy screening.
Keywords: Radiation dose; TIPS; ultrasound